Kreativ tafakkur tushunchasining falsafiy manbalardagi talqini - Sulaymanova, D.N (SCIENCE and SOCIETY, 2024)
This article argues that one of the main areas of training teachers of the new era through philosophical understanding of the concept of creative thinking is the need to focus on the disclosure of their creative potential, as well as the interpretation of the concept of creative thinking. Creative thinking in philosophical sources is reasonably analyzed.
Keywords: thinking; creative thinking; approach; philosophical; personality; perfection